Assembly of Colloidal Nanoparticles into Hollow Superstructures by Controlling Phase Separation in Emulsion Droplets. Issue 6 (30th March 2021) - Wu, Chaolumen; Lu, Zhenda; Li, Zhiwei; Yin, Yadong
Abstract : Template‐mediated self‐assembly of colloidal nanoparticles into secondary structures is of particular importance for exploring new materials with unique collective properties. However, the limited available templates and the poor control over the assembly of nanoparticles within the space defined by the templates drastically inhibit the preparation of the superstructures with the desired size and morphology. Herein, a general method to prepare submicron hollow superstructures by self‐assembling hydrophobic colloidal nanoparticles together with polymeric additives within oil‐in‐water emulsion droplets is reported. Upon evaporation of low boiling point oil, phase separation occurs to drive the assembly of nanoparticles at the polymer/water interface, producing a nanoparticle shell surrounding each polymeric core. Such core–shell structures can be converted into hollow superstructures of nanoparticles by stabilization with a silica coating and removal of the polymeric additives by solvent dissolution. Upon calcination, the silica layer can be further etched to release free‐standing hollow shells of nanoparticles. With its general applicability to the assembly of various nanoparticles, this method represents a new platform for the fabrication of diverse hollow superstructures toward broad applications that can take advantage of the collective properties of the nanoparticles and the hollow morphology of the assemblies. Abstract : A general strategy is developed for the fabrication of submicron hollow superstructures by controlling the phase separation of nanoparticles from polymer additives confined within an oil‐in‐water emulsion droplet. The resulting hollow superstructures can be further stabilized by calcination, producing water‐dispersible free‐standing hollow superstructures.